Advanced Learning As An Implicit Model Of Continuous Education - Tsaturyan, Armen (Զանգակ հրատ.)
By modeling and analyzing the levels of knowledge of students in school disciplines, the great didactic significance of more general and universal ideas in the process of forming students’ thinking during learning has been revealed. Presenting particularly important aspects of the process of generalization of students' knowledge and existing interpretations of one model of advanced learning, ways to implement the ideas of continuous education within the framework of fundamentalization and strengthening of the methodological approach of the educational process are identified. The application of the presented model of advanced learning allows to generalize fundamental ideas, universal concepts and methods, which are the basis for the formation of thinking in the following discipline by using general logical methods of scientific knowledge (analysis, synthesis, induction, deduction, modeling, analogues, etc.). The subject of the study is to reveal the fundamental possibilities of advanced learning in the process of implicit transfer of students' knowledge. The purpose of the article is to substantiate the development and implementation of an advanced learning model aimed at improving the quality of learning in the context of continuous education, based on the implicit transfer of student knowledge. It is shown that in advanced learning, the objects of advance are such fundamental ideas, concepts, and methodological approaches which in their essence are core for the process of knowledge transfer. Consistent application of advanced learning is an effective tool for generalizing students' knowledge which contributes to the formation of students' thinking. As a result, the concept of “Advanced learning as an implicit model of continuous education” was has been put forward.
Keywords: Education